PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ANAK DENGAN PENERAPAN PEMBERATAN PIDANA (KAJIAN TEORI HAK ASASI MANUSIA DAN PERLINDUNGAN ANAK) - Mompang L. Panggabean; Hendri Jayadi Pandiangan; David hutahaean (Fakultas Hukum Universitas Kristen Indonesia, 2021)
Child trafficking is criminal act of trafficking children who are not yet 18 years, including unborn children. Children as victims experience psychological, mental, physic, sexual, economic and social suffering as a result of the criminal act of trafficking in persons.Children as victims mmust be protected by applying criminal weight, to enforce the law effectively , protect children from becoming victims again (victimization), guaranteeing children’s right in the form of restitution and compensation. The application of criminal weighting for perpetrators of the crime of child trafficking is based on human rights analysis study and an analysis of child protection law. With the application of criminal weighting, it is hoped that child trafficking will decrease if it cannot be eliminated complete. Kata kunci: Perdagangan anak